All‐Solid‐State Planar Sodium‐Ion Microcapacitors with Multidirectional Fast Ion Diffusion Pathways. Issue 23 (4th October 2019) - Zheng, Shuanghao; Wang, Sen; Dong, Yanfeng; Zhou, Feng; Qin, Jieqiong; Wang, Xiao; Su, Feng; Sun, Chenglin; Wu, Zhong‐Shuai; Cheng, Hui‐Ming; Bao, Xinhe
Abstract: With the relentless development of smart and miniaturized electronics, the worldwide thirst for microscale electrochemical energy storage devices with form factors is launching a new era of competition. Herein, the first prototype planar sodium‐ion microcapacitors (NIMCs) are constructed based on the interdigital microelectrodes of urchin‐like sodium titanate as faradaic anode and nanoporous activated graphene as non‐faradaic cathode along with high‐voltage ionogel electrolyte on a single flexible substrate. By effectively coupling with battery‐type anode and capacitor‐type cathode, the resultant all‐solid‐state NIMCs working at 3.5 V exhibit a high volumetric energy density of 37.1 mWh cm −3 and an ultralow self‐discharge rate of 44 h from V max to 0.6 V max, both of which surpass most reported hybrid micro‐supercapacitors. Through tuning graphene layer covered on the top surface of interdigital microelectrodes, the NIMCs unveil remarkably enhanced power density, owing to the establishment of favorable multidirectional fast ion diffusion pathways that significantly reduce the charge transfer resistance. Meanwhile, the as‐fabricated NIMCs present excellent mechanical flexibility without capacitance fade under repeated deformation, and electrochemical stability at a high temperature of 80 °C because of using nonflammable ionogel electrolyte and in‐plane geometry. Therefore, these flexible planar NIMCs with multidirectional ion diffusion pathways hold tremendous potential for microelectronics. Abstract : All‐solid‐state planar sodium‐ion microcapacitors are constructed on a single substrate based on faradaic sodium titanate as anode and non‐faradaic activated graphene as cathode along with nonflammable high‐voltage ionogel electrolyte. The resultant microcapacitors possess the merit of multidirectional fast ion diffusion pathways and show high volumetric performance, remarkable flexibility, and high‐temperature stability.